Spatial, demographic and financial analysis of hospitalizations due primary care sensitive conditions: a new use of the indicator - Veloso, Márcio Antônio Alves (2024)
This article aimed to analyze the territorial origin, demographic and financial aspects and the frequency of occurrences of Hospitalizations due Primary Care Sensitive Conditions (HPCSC), that occurred in the public health system of Montes Claros, a municipality in the North of Minas Gerais, from 2017 to 2021. This is an ecological study with time series trend analysis developed from data of patients living in the city. Records from the Hospital Information System of the Information Technology Department of the Unified Health System (DATASUS), the Primary Care Information and Management System, and the digital cartographic base of the city council of Montes Claros (MG) were used. Regarding the results, the majority (18%) come from the city center region, with the most frequent diagnoses being Heart Failure (17.38%); Cerebrovascular Diseases (12.87%); and Bacterial Pneumonia (11.52%). The average cost per HPCSC was R$1,781.23, with the highest cost being related to Angina (R$4,859.04). The demographic profile of those hospitalized for HPCSC is made up of a slight majority of men (50.62%) and the largest age group was 60 to 79 years old (37.19%). Regarding skin color, 62.94% of hospitalizations included patients who declared themselves mixed race. There was a concentration of ACSCs from the central region, with a predominance of elderly people and cardiovascular causes. The results can help health managers in adopting specific and more effective measures.